Fracture resistance of veneers in premolars - Linhares, Ludmilla Azevedo; Pottmaier, Larissa Fernanda; Lopes, Guilherme Carpena (European Journal of Dentistry, 2018)
Objective: The purpose of the study was to compare the fracture resistance of ceramic veneers and composite resin veneers with and without dental preparation. Materials and Methods: Forty freshly extracted mandibular premolars were selected and randomly assigned into four groups (n = 10): Group NPR = no dental preparation and direct veneer with 0.2 mm thick composite resin (Amelogen Plus, Ultradent); Group NPC = no dental preparation and 0.2 mm thick lithium disilicate ceramic veneer (IPS e.max Press, Ivoclar Vivadent); Group P2C = Tooth preparation of 0.2 mm and 0.2 mm thick ceramic veneer (IPS e.max Press); and Group P5C = Tooth preparation of 0.5 mm and 0.5 mm-thick ceramic veneer (IPS e.max Press). In all groups, the restorations covered 1 mm of the occlusal surface of the buccal cusp, and the thickness of this area was the same of the buccal area (0.2 mm or 0.5 mm). After the luting procedure, all groups were thermocycled (10,000 cycles, 5°C–55°C) and subjected to fracture resistance test under compression (Instron 4444 with a crosshead speed of 0.5 mm/min). The mode of failure analysis was performed under a ×10 magnification. Data were subjected to one-way ANOVA and Duncan's post hoc test (P < 0.05). Results: The mean fracture resistance (men ± standard deviation) was NPR = 690.33 ± 233, NPC = 790.52 ± 408, P2C = 1131.34 ± 341, and P5C = 983.56 ± 202. There were significant differences of the fracture resistance values between all groups (P = 0.013). NPR and NPC groups showed mean values of fracture resistance significantly lower than P2C. However, P5C presented intermediate values without a significant difference from the other groups. The mode of failure for all groups was mixed (60%), cohesive failures (20%), root failures (15%), and adhesive failures (5%). Conclusion: Minimally invasive tooth preparation (0.2-mm) allowed to achieve higher fracture resistance in premolars restored with lithium disilicate ceramic veneers. Attention should be given to the 0.5 mm preparation since catastrophic fractures only happened when this preparation depth was performed.
Keywords: Ceramic veneers; fracture resistance; lithium disilicate; mode of failure; resin composite